2022
DOI: 10.1128/jb.00078-22
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced F 420 -Dependent Nitrite Reductase in an Anaerobic Methanotrophic Archaeon

Abstract: Coenzyme F 420 -dependent sulfite reductase (Fsr) protects methanogenic archaea inhabiting deep-sea hydrothermal vents from the inactivation of methyl coenzyme M reductase (Mcr), one of their essential energy production enzymes. Anaerobic methanotrophic archaea (ANME) that oxidize methane and rely on Mcr, carry Fsr homologs that form a distinct clade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 93 publications
1
10
0
Order By: Relevance
“…1) 15 . In the absence of DsrC, DsrAB releases some S 2− , as well as the reaction intermediates trithionate and thiosulfate [15][16][17] .…”
Section: The F 420 H 2 -Oxidase Domain Flanks a Sulfite Reductase Corementioning
confidence: 99%
“…1) 15 . In the absence of DsrC, DsrAB releases some S 2− , as well as the reaction intermediates trithionate and thiosulfate [15][16][17] .…”
Section: The F 420 H 2 -Oxidase Domain Flanks a Sulfite Reductase Corementioning
confidence: 99%
“…The Arg 98 , Arg 170 , Lys 211 and Lys 213 of Af Dsr are fully conserved in Mj FsrI (Arg 355 , Arg 423 , Lys 460 and Lys 462 [15, 31]) and therefore Mj FsrI employed a common chemical mechanism for reducing sulphite and nitrite; the recently available crystal structure of Mj FsrI indeed shows that Arg 355 , Arg 423 , Lys 460 and Lys 462 are involved in the binding of sulphite and two water molecules at the active site of this protein [31]. The ability of Mj FsrI to reduce hydroxylamine (NH 2 OH) indicated that the Fsr-catalysed reduction of nitrite proceeded through the intermediate formation of hydroxylamine and this sequence is also seen with the other sulphite/nitrite reductases [17, 18, 20, 21]. The enzyme was efficient in the utilization of the F 420 H 2 -derived reducing equivalents as it exhibited almost 100 % recovery of this resource into ammonia, the product.…”
Section: Discussionmentioning
confidence: 99%
“…The assays for FNiR, Fsr and F 420 H 2 -dependent hydroxylamine reductase were performed anaerobically using reduced F 420 (F 420 H 2 ) as the electron donor and respective electron acceptors, which were nitrite, sulphite and hydroxylamine, following a previously described procedure [15,17,27]. Briefly, this procedure involved spectrophotometric monitoring of the oxidation of F 420 H 2 at 400 nm, and an extinction coefficient value of 25 mM −1 cm −1 for F 420 was used to calculate the reaction rate [28].…”
Section: Enzyme Activity and Protein Assays And Sds-pagementioning
confidence: 99%
See 2 more Smart Citations